2019
DOI: 10.1039/c8sm01785a
|View full text |Cite
|
Sign up to set email alerts
|

Dip-coating of suspensions

Abstract: Withdrawing a plate from a suspension leads to the entrainment of a coating layer of fluid and particles on the solid surface. In this article, we study the Landau-Levich problem in the case of a suspension of non-Brownian particles at moderate volume fraction 10% < φ < 41%. We observe different regimes depending on the withdrawal velocity U , the volume fraction of the suspension φ, and the diameter of the particles 2 a. Our results exhibit three coating regimes. (i) At small enough capillary number Ca, no pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
75
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 56 publications
18
75
1
1
Order By: Relevance
“…Figure 2(c) reports the evolution of h with the withdrawal velocity for the same suspension. From low to large velocities, it reveals three distinct coating regimes, as also reported very recently by Gans et al (2019). (i) a 'no particle entrainment' regime, where the film is much thinner than d, (ii) a 'monolayer' regime, where the film thickness is of the order of the particle diameter (h d) and is essentially independent of U , (iii) a 'thick film' regime, where the film thickness is much larger than the particle size (h d) and increases with increasing U .…”
Section: G G 8 D I R 7 < / L a T E X I T > < L A T E X I T S H A 1 _ supporting
confidence: 82%
See 1 more Smart Citation
“…Figure 2(c) reports the evolution of h with the withdrawal velocity for the same suspension. From low to large velocities, it reveals three distinct coating regimes, as also reported very recently by Gans et al (2019). (i) a 'no particle entrainment' regime, where the film is much thinner than d, (ii) a 'monolayer' regime, where the film thickness is of the order of the particle diameter (h d) and is essentially independent of U , (iii) a 'thick film' regime, where the film thickness is much larger than the particle size (h d) and increases with increasing U .…”
Section: G G 8 D I R 7 < / L a T E X I T > < L A T E X I T S H A 1 _ supporting
confidence: 82%
“…Motivated by film deposition and selfassembly of colloids for surface patterning, lithography or optical applications (Yu & Zhang 2013) much attention has been devoted to colloidal particles suspended in a volatile liquid, for which evaporation is often a dominant factor (Dimitrov & Nagayama 1996;Ghosh et al 2007;Buchanan et al 2007;Le Berre et al 2009;Faustini et al 2010;Jing et al 2010;Brewer et al 2011;Berteloot et al 2013;Jung & Ahn 2013). However, much fewer studies have considered suspensions of larger particles (∼ 100 µm) or low volatility liquids (Kao & Hosoi 2012;Colosqui et al 2013;Gans et al 2019). In these cases the < l a t e x i t s h a 1 _ b a s e 6 4 = " i L g n T l y 6 Y f p o X p Y J N G I c C O 2 f B B 4 = " > A A A B 4 n i c b Z D L T g J B E E V r 8 I X 4 Q l 2 6 6 U h M X J E Z Y 6 J L o h u X k A i S w I T 0 N D X Q o e e R 7 h o T M u E H d G X U n Z / k D / g 3 N j g L B e / q d N 3 b S d 0 K U i U N u e 6 X U 1 p b 3 9 j c K m 9 X d n b 3 9 g + q h 0 c d k 2 R a Y F s k K t H d g B t U M s Y 2 S V L Y T T X y K F D 4 E E x u 5 / 7 D I 2 o j k / i e p i n 6 E R / F M p S C k x 2 1 R o N q z a 2 7 C 7 F V 8 A q o Q a H m o P r Z H y Y i i z A m o b g x P c 9 N y c + 5 J i k U z i r 9 z G D K x Y S P s G c x 5 h E a P 1 8 s O m N n Y a I Z j Z E t 3 r + z O Y + M m U a B z U S c x m b Z m w / / 8 3 o Z h d d + L u M 0 I 4 y F j V g v z B S j h M 3 7 s q H U K E h N L X C h p d 2 S i T H X X J C 9 S s X W 9 5 b L r k L n o u 6 5 d a 9 1 W W v c F I c o w w m c w j l 4 c A U N u I M m t E E A w j O 8 w b s z d J 6 c F + f 1 J 1 p y i j / H 8 E f O x z f B 2 4 q A < / l a t e x i t > < l a t e x i t s h a 1 _ b a s e 6 4 = " i L g n T l y 6 Y f p o X p Y J N G I c C O 2 f B B 4 = " > A A A B 4 n i c b Z D L T g J B E E V r 8 I X 4 Q l 2 6 6 U h M X J E Z Y 6 J L o h u X k A i S w I T 0 N D X Q o e e R 7 h o T M u E H d G X U n Z / k D / g 3 N j g L B e / q d N 3 b S d 0 K U i U N u e 6 X U 1 p b 3 9 j c K m 9 X d n b 3 9 g + q h 0 c d k 2 R a Y F s k K t H d g B t U M s Y 2 S V L Y T T X y K F D 4 E E x u 5 / 7 D I 2 o j k / i e p i n 6 E R / F M p S C k x 2 1 R o N q z a 2 7 C 7 F V 8 A q o Q a H m o P r Z H y Y i i z A m o b g x P c 9 N y c + 5 J i k U z i r 9 z G D K x Y S P s G c x 5 h E a P 1 8 s O m N n Y a I Z j Z E t 3 r + z O Y + M m U a B z U S c x m b Z m w / / 8 3 o Z h d d + L u M 0 I 4 y F j V g v z B S j h M 3 7 s q H U K E h N L X C h p d 2 S i T H X X J C 9 S s X W 9 5 b L r k L n o u 6 5 d a 9 1 W W v c F I c o w w m c w j l 4 c A U N u I M m t E E A w j O 8 w b s z d J 6 c F + f 1 J 1 p y i j / H 8 E f O x z f B 2 4 q A < / l a t e x i t > < l a t e x i t s h a 1 _ b a s e 6 4 = " i L g n T l y 6 Y f p o X p Y J N G I c C O 2 f B B 4 = " > A A A B 4 n i c b Z D L T g J B E E V r 8 I X 4 Q l 2 6 6 U h M X J E Z Y 6 J L o h u X k A i S w I T 0 N D X Q o e e R 7 h o T M u E H d G X U n Z / k D / g 3 N j g L B e / q d N 3 b S d 0 K U i U N u e 6 X U 1 p b 3 9 j c K m 9 X d n b 3 9 g + q h 0 c d k 2 R a Y F s k K t H d g B t U M s Y 2 S V L Y T T X y K F D 4 E E ...…”
Section: Introductionmentioning
confidence: 99%
“…The capillary threshold for particle entrainment, Ca * , depends on the particle size through the Bond number of the particle Bo = (a/ c ) 2 , Ca * = 0.24 Bo 3/4 [33,36]. Recently, this relationship has been experimentally demonstrated across different particle sizes and working fluids [35,37]. Note that this transition does not correspond to an inertial effect, as Re 1 for all of the experimental data.…”
mentioning
confidence: 77%
“…Recent results have shown that particle entrainment in dip coating of suspensions only occurs above a threshold velocity [33][34][35][36]. This is due to a competition of forces at the meniscus, which forms where the substrate meets the liquid-air interface.…”
mentioning
confidence: 99%
“…Dip coating is a feasible and scalable method for creating large‐area arrays of NPL films, which does not require a high concentration of dispersions as compared to spin coating . By carefully controlling the withdraw speed and solvent volatility, a continuous NPL film with tunable thickness is hopefully to be attainable.…”
Section: Film Formation Of Perovskites' Emitting Layermentioning
confidence: 99%